1997
DOI: 10.1007/s004380050589
|View full text |Cite
|
Sign up to set email alerts
|

Gene activation at a distance and telomeric silencing are not affected by yeast histone H1

Abstract: Until recently, it was believed that the budding yeast Saccharomyces cerevisiae has no histone H1 gene. However, a search of the yeast genome database revealed a possible H1 homologue of 258 amino acids, termed yeast histone H1 (HHO1). The protein shows 36% identity to the human H1 core domain over a stretch of 93 amino acids. Unlike other H1 proteins, Hho1p has a second possible core domain which shows 43% identity to the first core domain. Since vertebrate H1 histone had been implied in gene repression as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
5
32
4
Order By: Relevance
“…These results contrast with earlier reports that failed to detect any effect of Hho1p on silencing (Escher and Schaffner 1997;Patterton et al 1998). We believe there are two reasons for these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results contrast with earlier reports that failed to detect any effect of Hho1p on silencing (Escher and Schaffner 1997;Patterton et al 1998). We believe there are two reasons for these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…The deletion did not affect TRP1 or URA3 expression. This result is consistent with earlier findings that failed to detect an effect of HHO1 deletion on the silencing of subtelomeric reporter genes (Escher and Schaffner 1997;Patterton et al 1998). From this set of experiments we conclude that HHO1 does not act directly on the reporter genes, nor does it affect telomeric silencing.…”
Section: Resultssupporting
confidence: 93%
“…1, compare 2 with 1, 10 with 9, and 14 with 13 on FOA). This is consistent with previous studies that revealed no role of HHO1 in transcriptional silencing (14,18,21). However, it is formally possible that Hho1p plays a role in silencing that is redundant with or antagonistic to functions of other factors, such as histones, involved in the formation and/or maintenance of silent chromatin.…”
Section: Deletion Of Hho1 Suppresses the Defect In Transcriptional Sisupporting
confidence: 93%
“…However, deletion of HHO1 seems to have no effect on silencing at HM loci, telomeres, and rDNA (14,18,21,23). On the other hand, we found that overexpression of HHO1 has an inhibitory effect on silencing (28).…”
mentioning
confidence: 89%
See 1 more Smart Citation